Cyclone Impacts on Coral Reef Communities in Southwest Madagascar - Carter, Amber L.; Gilchrist, Hannah; Dexter, Kyle G.; Gardner, Charlie J.; Gough, Charlotte; Rocliffe, Steve; Wilson, A. Meriwether W. (Frontiers in Marine Science, 2022)
Tropical cyclones can cause severe destruction of coral reefs with ecological consequences for reef fish communities. Ocean warming is predicted to shorten the return interval for strong tropical cyclones. Understanding the consequences of cyclone impacts on coral reefs is critical to inform local-scale management to support reef resilience and the livelihood security of small-scale fishing communities. Here, we present the first analysis of a tropical cyclone disturbance on coral reefs in Madagascar. We investigate the impact of Cyclone Haruna (category 3 Saffir-Simpson scale) in February 2013 on coral communities, both adults and recruits, and explore the relationship between the severity of cyclone impact with cyclone parameters (wind speed, duration of storm impact and distance from cyclone track) and environmental variables (reef type and reef depth). We use survey data collected as part of a long-term citizen science monitoring programme at 21 coral reef sites between 2012 and 2015 in the Velondriake Locally Managed Marine Area along Madagascar’s southwest coast. Coral cover declined at 19 sites, however damage was spatially heterogeneous ranging from a decrease in coral cover of 1.4% to 45.8%. We found the severity of cyclone damage related to: distance from the cyclone track, duration of cyclone impact and reef depth. The taxonomic and morphological composition of coral communities was significantly different after the cyclone. Notably, there was a decrease in the dominance of branching morphologies, and an increase in the relative abundance of encrusting and massive morphologies. Two years after Cyclone Haruna, mean coral cover had increased and the density of coral recruits increased to above pre-cyclone levels indicating the potential recovery of coral populations. However, recovery to pre-disturbance community composition will likely be hindered by the increasing occurrence of acute and chronic disturbance events.